Neuro-ophthalmological symptoms in pituitary apoplexy (Ukrainian Journal of Ophthalmology, 2025)
Background: Neuro-ophthalmological symptoms in patients with pituitary apoplexy were subjected to analysis. Impaired circulation in pituitary adenoma causes an atypical clinical course of the disease which makes the early diagnosis and provision of medical care difficult. Neuro-ophthalmological manifestations of the disease include loss of vision, visual field defects and oculomotor disturbances. Since the visual loss may present as unilateral or bilateral blindness, the field of this disease is of special importance.Purpose: To investigate neuro-ophthalmological symptoms in patients with pituitary apoplexy before and after treatment.Materials and Methods: Ninety patients with pituitary apoplexy were under surveillance at the Romodanov Neurosurgery Institute between 2014 and 2017. Of these, 44 patients (88 eyes) had visual loss and/or visual field defects, and were included in the main group of the study. Patients underwent clinical and neurological, neuro-ophthalmological, and otoneurological examination (including neuroimaging studies).Results: Acute pituitary apoplexy (54.5% of patients) was characterized by sudden onset of presumably symmetric (50% of patients) chiasmal syndrome, and manifested by mildly or moderately impaired BCVA (39.6% of eyes) and sensitivity to light (60% of eyes), partial bitemporal hemianopia, oculomotor disturbances and absence of ophthalmoscopic changes. In addition, surgical treatment resulted in restoration of visual acuity and visual field in 27 (56.3%) eyes.Subacute pituitary apoplexy (45.5% of patients) was characterized by a gradual development of chiasmal syndrome, with a history of sudden visual function loss, and by presumably severe or very severe visual acuity loss (65% of eyes), light sensitivity loss (67.5% of eyes), and development of primary descending optic nerve atrophy (70% of eyes). In addition, surgical treatment resulted in improvements in visual function in most (65%) eyes; however, compared with acute pituitary apoplexy, a complete restoration of visual function was less frequently observed (15%).Conclusion: Pituitary apoplexy is one of the causes of acute visual loss in neurosurgical disorders. In acute pituitary apoplexy, early diagnosis and surgical treatment resulted in stabilization or improvement in visual acuity from 0.54±0.05 to 0.81±0.03 (p < 0.05), and improvement in visual field defects (as assessed by MD values) from 9.05±0.99 to 4.18±0.81 dB (p < 0.05).
Keywords: pituitary adenoma; pituitary apoplexy; chiasmal syndrome; optic nerve atrophy